SO_GERICHTE ZZ.1977.15 vom 17. November 1977 , Anforderungen an die Stabilität der Ladung eines Anhängerzuges - SO Obergericht (1977)
Art. 30 Abs. 2, Art. 90 Ziff. 1 SVG. Anforderungen an die Stabilität der Ladung eines Anhängerzuges.